Предмет: Алгебра,
автор: ksenia8520
Запишіть у вигляді многочлена: 1).(х+5)(х-5)-(х-3)^2
2). (3х^4+2х)^2
ПОМОГИИИТЕ СРОЧНО!!!!
Ответы
Автор ответа:
1
Ответ:
1) х²-5²-(х²-6х+9)=х²-25-х²+6х-9=6х-34
2)3х⁸+12х⁵+4х²
Автор ответа:
1
Відповідь:
Пояснення:
1 ) (х+5)(х-5) - (х-3)²= x² - 25 - ( x² - 6x + 9 ) = x² - 25 - x² + 6x - 9 =
= 6x - 34 ;
2) (3х⁴+2х)² = 9x⁸ + 12x⁵ + 4x² .
Похожие вопросы
Предмет: История,
автор: mansurisengaliev
Предмет: Русский язык,
автор: nuadov
Предмет: Геометрия,
автор: Milly2014
Предмет: Физика,
автор: meelenabelmehova